Rainwater Quality Measurements in the Area of Bricks Manufacturing at Kajhu Aceh Besar - Sarina .; Nurul Mafazi; Riski Rahmania; Elin Yusibani (Journal of Aceh Physics Society, 2015)
The study of rainwater quality measurement has been done in brick manufacturing area of Kajhu, Aceh Besar. The measurements are taking place in the three different places when the rain fall from the sky in Kajhu area. The physical parameters that will be measured are pH, TDS, conductivity and potential of electricity.